2011
DOI: 10.3892/mmr.2011.497
|View full text |Cite
|
Sign up to set email alerts
|

Association study between the -866G/A polymorphism in the promoter of uncoupling protein-2 gene and polycystic ovary syndrome

Abstract: Abstract. Polycystic ovary syndrome (PCOS) is a disorder characterized by hyperandrogenism, chronic oligoanovulation and insulin resistance. A number of women with PCOS are obese and exhibit abnormal phenotypes, including high levels of androgens, an irregular menstrual cycle and increased hair growth. Studies on obese PCOS patients have proven the crucial role that obesity plays in insulin resistance and hyperinsulinemia. The uncoupling protein (UCP) gene is one of the genes known to have a strong association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our findings revealed that the AA genotype of rs660339 was a risk factor of T2DM for overweight subjects (OR = 1.48) but a protective factor for those with normal weight (OR = 0.54). Both UCP2 and overweight/obesity are associated with insulin resistance [ 21 , 36 , 37 ], a fundamental aspect of the etiology of T2DM. It is unknown however, why AA genotype of rs660339 influences T2DM differently in overweight and normal weight people.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that the AA genotype of rs660339 was a risk factor of T2DM for overweight subjects (OR = 1.48) but a protective factor for those with normal weight (OR = 0.54). Both UCP2 and overweight/obesity are associated with insulin resistance [ 21 , 36 , 37 ], a fundamental aspect of the etiology of T2DM. It is unknown however, why AA genotype of rs660339 influences T2DM differently in overweight and normal weight people.…”
Section: Discussionmentioning
confidence: 99%